Pengaruh Net Profit Margin (NPM), Earning Per Share (EPS), Produk Domestik Bruto (PDB) Dan Inflasi terhadap Harga Saham Perusahaan Yang Terdaftar di Jakarta Islamic Index (JII) Tahun 2014-2018 - Lilik Masliyah; Akhmad Sobrun Jamil; Muhammad Mujtaba Mitra Zuana (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2020)
This study aims to determine the effect of Net profit margin (NPM) and earnings per share (EPS), gross domestic product (PDB) and inflation on share prices of companies listed on the Jakarta Islamic Index (JII) during 2014-2018, both partially and simultaneously. The population in this study are all companies that are consistently listed on the Jakarta Islamic Index for 5 periods. The samples in this study were 15 companies obtained by purposive sampling technique. Analysis of the data used is panel data analysis. The results showed that the NPM variable partially had a significant effect on stock prices, while EPS, GDP and inflation had no significant effect. Simultaneously the variables NPM, EPS, GDP and inflation affect stock prices.